2022
DOI: 10.3389/fendo.2022.858417
|View full text |Cite
|
Sign up to set email alerts
|

Brown Adipose Tissue Prevalence Is Lower in Obesity but Its Metabolic Activity Is Intact

Abstract: Due to its high metabolic activity, brown adipose tissue (BAT) has become a promising target for the development of novel treatment concepts for metabolic disease. Despite several reports of a negative association between the presence of active BAT and obesity, very little is known about the quantitative and qualitative differences of BAT in lean and obese individuals. Systematic studies directly comparing cold-induced BAT activity in leanness and obesity are currently lacking. Here we studied BAT mass and fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…These findings support the recommendation to further test both the isomers and/or their combination in preclinical studies to investigate whether these molecules can have positive effects in weight loss. Indeed, recent observations from Kulterer and coworker [ 56 ] demonstrated that BAT is less frequently detected in obese rather than in lean people. They also highlighted that BAT is associated with visceral adiposity rather than with total body fat content per se.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the recommendation to further test both the isomers and/or their combination in preclinical studies to investigate whether these molecules can have positive effects in weight loss. Indeed, recent observations from Kulterer and coworker [ 56 ] demonstrated that BAT is less frequently detected in obese rather than in lean people. They also highlighted that BAT is associated with visceral adiposity rather than with total body fat content per se.…”
Section: Discussionmentioning
confidence: 99%
“…5 An inverse correlation exists between the amount of BAT and the body mass index, percentage of total body fat, and volume of WAT. 19 Greater activity of BAT is associated with less fat content within WAT, subcutaneous fat depots, and the liver. 5,37 The WAT in patients with obesity has less capability for releasing interleukin 13 compared with that in their lean counterparts, which would subsequently result in reduced conversion of macrophages from the M1 to the M2 phenotype.…”
Section: The Controversial Impact Of Obesity On Critical Illnessmentioning
confidence: 99%
“…18 Increasing amounts of BAT are associated with reduced body mass index and visceral adipose tissue. 5,19 Those who have a greater amount or larger deposits of BAT tend to have less fat content in their visceral adipose tissue, subcutaneous fat tissue, or liver. 5 BAT is characterized by the increased expression of UCP-1, which causes the uncoupling of the electron transport chain from the synthesis of ATP.…”
Section: Batmentioning
confidence: 99%
“…BAT also has a role in adiposity and its metabolic activity is inversely related to BMI [ 14 , 15 ]. Although the prevalence of active BAT decreases with obesity [ 16 ], a recent study reported that obese individuals with active BAT have a healthier metabolic phenotype [ 17 ]. Besides white and brown adipocytes, today we also recognize beige, pink, and yellow adipocytes, all with distinct functions that are described elsewhere [ 18 ].…”
Section: Adipose Tissue Remodeling Impairment Of Redox Homeostasis An...mentioning
confidence: 99%